Impacts of climate change, policies and adaptation technologies on rice productivity across agro ecological zones in Nigeria - Baba, Mohammed Abdullahi (2021)
African countries have the lowest food productivity compared to other regions of the world. Particularly important is Nigeria’s rice sector, which although currently the largest producer in Africa yet it is still a major world importer. This is largely attributed to the low productivity of rice which varies across six Agro Ecological Zones (AEZs) that marks the boundaries in terms of climate, soil and vegetation types. In the phase of high food insecurity and environmental concerns, improving productivity is considered a more sustainable approach. This study assessed multiple dimensions of climate factors (carbon dioxide, rainfall, temperature and flood); adaptation of technologies (irrigation and dummy of National Adaptation Strategies and Plan of Action on Climate Change in Nigeria (DumNASPA)) and policies (trade policy, corruption and government stability) as rice productivity determinants across AEZs. Data collection covers six AEZs from 1980 to 2018. After a series of diagnostic test, the unit root test, the cross-sectional dependence test and the Hausman test, the panel Autoregressive Distributive Lag (ARDL) model particularly the pooled mean group (PMG) model was used to examine the long-run and short-run impact of factors in the model. The long-run result revealed that, three climate factors (carbon dioxide, temperature, and rainfall) and irrigation capacity have a positive and significant impact on rice productivity. Trade policies and corruption were also positive and significant. In the short run, the impact of the factors varies across AEZs in Nigeria. While, based on the long-run PMG result, the positive effect of climate change factors, irrigation capacity, and import tariffs supports the increase in rice productivity. Interacting corrupt practices with fertilizer usage indicated a positive effect on rice productivity. This practice will actually increase production costs and in turn reduce the profits of paddy farmers. Therefore, policy making should consider the significant factors in each AEZ.